Evaluasi Kualitas Dan Kuantitas Penggunaan Antibiotik Pada Penderita Demam Tifoid Di Rawat Inap Rs An-Nisa Tangerang - Winarni, Gandes; Putri, Annisa Septyana; Aisyah, Rizqa Nur (PHRASE (Pharmaceutical Science) Journal, 2025)
Typhoid fever is an infectious disease caused by Salmonella typhi and is still a health problem in Indonesia. The rational use of antibiotics can increase the risk of resistance. This study aims to evaluate the quality and quantity of antibiotic use in typhoid fever patients in the inpatient ward of An-Nisa hospital Tangerang. The method used was descriptive research with retrospective data collection from patient medical records. The sample in the study was 67 patients who met the inclusion criteria. The quality of antibiotic use was analyzed using the Gyssens method based on the Kemenkes of 2013 and Permenkes No. 28 of 2021, while the quality of antibiotic use was analyzed using the ATC/DDD (Defined Daily Dose) method based on theWHO DDD values. The results of the study showed that only 12,72 of antibiotic use was rational (category 0), while the rest was irrational, especially in category IIIB (duration of use too short) by 36,99 and category V (no indication) by 7,51%, category IVC (cheaper antibiotic) by 4,62%, category IIB (inappropriate interval) by 4,05% and category IIC (route of administration) by 2,86%. The most commonly used antibiotic was Cefixime with the highest DD/100 patient-days value of 126,57 and followed by Ceftriaxone with a DDD/100 patient-days value of 75,12. The conclusion of this study shows that there is a need to improve the accuracy of antibiotic administration, especially in duration, dose, and indication of use, to prevent the emergence of antibiotic resistance in the future.